PENGARUH VARIABEL FUNDAMENTAL PERUSAHAAN TERHADAP RISIKO SISTEMATIS SAHAM PADA PERUSAHAAN - PERUSAHAAN YANG TERDAFTAR DI INDEKS KOMPAS 100 - Guntoro, Hendra B1021131027 (Jurnal Manajemen Update, 2017)
The systematic risk is the inseparable component in investment. Systematic risk can gauged by using beta. Beta is the indicator of share?s price volatility, investor perspective measurement toward company and criteria indicator of company merger or acquisition activity. This research aims to scrutinize thoroughly impact of corporate fundamental variable: Total Asset Growth, Total Debt to Asset Ratio and Asset Size on corporate?s systematic risk in firm?s listed in Kompas 100. This research applies quantitative research method, in which research is based on the positivism philosophy aimed to carry out examination on population and sample. This research sampling method acquires secondary data provided by those corporates, capital market institution and another trusted source.  This study data is purposive sampling, in which the sample used have to fulfill the required criterions: 1) The firms listed in Kompas 100 index during research period, 2) The complete data for financial reports is available during the research period, 3) The firms listed in Kompas 100 index never suspended during research period. The firms used as the sample are the firms listed in Kompas 100 index during the period of 2011 ? 2015. The sample selection is based on the development of the Total Asset Growth, Debt to Asset Ratio, as well as Asset Size. After the selection, the writer garners the total sample of 37 firms which are able to fulfill the requirements as the sample. In this study, the writer used the panel regression estimation model by using the Random Effect Model (REM) or Error Component Model (ECM) approach. Whereas the hypothesis was tested by using the parametric statistic testing of Paired Sample T-Test. The outcome of the study shows that the Total Asset Growth negatively affects the systematic risk, the Debt to Asset Ratio is found to have negative impact on the systematic risk, the asset size affects positively impact on systematic risk.